ORGANIZING STUDENTS’ INDEPENDENT LEARNING ACTIVITIES TO DEVELOP PROFESSIONAL COMPETENCIES - Khalimjonova Mavludahon O‘ktamjon kizi, (TADQIQOTLAR, 2026)
Abstract:  This  article  explores  the  theoretical  and  practical  aspects  of organizing  students’  independent  learning  activities  to  enhance  their  professional competencies.  In  the  context  of  contemporary  education,  fostering  independent learning  skills  has  become  a  critical  factor  in  preparing  students  for  complex professional  environments.  The  study  examines  various  pedagogical  strategies, emphasizing the role of self-directed learning, reflective practices, and competency-based approaches. The research synthesizes findings from recent studies to establish a conceptual framework that links independent learning with the development of critical professional  skills,  including  problem-solving,  analytical  thinking,  and  practical application. The results highlight the effectiveness of structured independent learning tasks,  digital  tools,  and  personalized  learning  pathways  in  promoting  the  holistic development of students’ professional competencies. The implications of this study are relevant  for  curriculum  designers,  educators,  and  policymakers  aiming  to  integrate autonomous learning methodologies into professional education.